Obesity attenuates force-induced tooth movement in mice with the elevation of leptin level: a preliminary translational study - Yan, Boxi (Am J Transl Res, 2018)
Increasing number of patients with high body-mass index (BMI) are encountered in the orthodontic clinic with the growing prevalence of obesity and overweight worldwide. Some clinical studies found that the rate of orthodontic tooth movement (OTM) in obese patients decreased. However, how obesity can impact OTM has not been determined yet. Here, we used the high-fat diet (HFD) induced obese mouse model to translate this clinical problem to the basic research, and back to exploring the potential clinical applications. C57BL/6J mice were fed with high-fat diet (HFD) for 5 weeks to induce obesity and orthodontic nickel-titanium springs were applied to the upper first molars to establish OTM model. The serum level of leptin was tested by ELISA. Mouse macrophage cell line RAW264.7 cells were used as osteoclast progenitor cells stimulated by sRANKL with the presence or absence of letpin in vitro. TRAP staining was used to detect osteoclasts. Leptin was administrated intraperitoneally in mice to determine whether it can affect OTM in vivo. In obese mice, we found that OTM was attenuated and the number of osteoclasts decreased with the elevated serum level of leptin. Mechanically, we confirmed that leptin inhibited osteoclastogenesis and osteoclast functional genes expression. To translate our findings back to potential applications, we then revealed the administration of leptin could decrease OTM in wild type mice along with the decreased number of TRAP-positive osteoclasts. Taken together, these results demonstrated that the elevated level of leptin in obese mice was able to inhibit osteoclastogenesis and decrease OTM. Administration of leptin could inhibit molar mesial movement and possessed the potential to be a clinical anchorage reinforcement method.